2022
DOI: 10.53378/352868
|View full text |Cite
|
Sign up to set email alerts
|

Math Anxiety and Mathematical Representations of Grade 7 Students

Abstract: Naturally, students are afraid to learn Mathematics that progresses as a fear of getting things wrong. This study utilizes the descriptive-correlational research design to test how the math anxiety and mathematics are connected to each other. Forty-two (42) Grade 7 students participated in the study during the school year 2020-2021. It used a researcher-made survey questionnaire on math anxiety and an examination on mathematical representations through modular learning. The math anxiety is indicated by mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…On the other hand, students can be afraid of learning mathematics which develops as a fear of making mistakes. However, students have high anxiety about mathematics (Escarez Jr. & Ching, 2022). The study showed that involving students in estimating HLR DLTI with the AaL approach could reduce the fear of being late in learning mathematics by 53%.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, students can be afraid of learning mathematics which develops as a fear of making mistakes. However, students have high anxiety about mathematics (Escarez Jr. & Ching, 2022). The study showed that involving students in estimating HLR DLTI with the AaL approach could reduce the fear of being late in learning mathematics by 53%.…”
Section: Discussionmentioning
confidence: 99%
“…Having higher interest levels has been observed to correspond with increased engagement in crucial cognitive processes such as attention, persistence, perceived competence, and utilization of effective learning strategies. These cognitive processes, in turn, have been identified as potential mediators and predictors of academic achievement [3,5,6,[9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the innovations made by the international and local education system, students still considered mathematics the most challenging subject (Escarez & Ching, 2022) specifically problem-solving (Nurjamaludin et al, 2021). This problem is evident in the Program for International Student Assessment (PISA) 2018, where the Philippines came in last place out of 79 countries in mathematics (OECD, 2019).…”
Section: Introductionmentioning
confidence: 99%